United Nations Psychology Day 2021 Focused on Post-Pandemic Rebuilding - Priyadharshany Sandanapitchai; Harold Takooshian (Peoples' Friendship University of Russia (RUDN University), 2021)
In the wake of the unprecedented global COVID-19 lockdowns in 2020, the Psychology Coalition at the United Nations (PCUN) managed to continue to pursue its mission, to apply psychological science to global issues at the UN. This two-part report offers a concise overview of (a) recent PCUN activities in 2020-2021, and (b) the PCUNs 14th annual Psychology Day at the UN on April 15, 2021, which focused on Psychological Contributions to Building Back Better in a Post-Pandemic World.